1962
DOI: 10.1002/j.1537-2197.1962.tb14924.x
|View full text |Cite
|
Sign up to set email alerts
|

The Genus Collinsia. Xvi. Supernumerary Chromosomes

Abstract: DHILLON, T. S., and E. D. GARBER. (U. Chicago, Chicago, Ill.) The genus Collinsia. XVI. Super. numerary chromosomes. Arner, Jour. Bot. 49(2): 168-170. 1%2.-The pairing and transmission of supernumerary chromosomes in Collinsia solitaria and in hybrids between C. sparsiflora subsp.arvensis and C. bruceae were studied. Two supernumerary chromosomes usually formed a bivalent with 1 chiasma at metaphase I; 4 supernumerary chromosomes occasionally yielded a trivalent and univalent at this stage. Plants with 2-4 sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1964
1964
1964
1964

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…pl. : DHILLON and GARBER 1962; o Anthoxanthum aristatum: OsTERGREN 1949; o Festuca arundinacea: BosE MARK 1957; o F estuca pratensis : BosEMARK 1957; o Phleum phleoides: BosEMARK 1957; o Alopecurus pratensis: BosEMARK 1957; o Briza media: BosEMARK 1957; o Holcus lanatus: BosEMARK 1957. The two cases of Phleurn phleoides and P. nodosum (BosEMARK 1957) deserve attention. While the first shows preferential distribution, the second does not present such a phenomenon.…”
Section: Secale Typementioning
confidence: 99%
See 1 more Smart Citation
“…pl. : DHILLON and GARBER 1962; o Anthoxanthum aristatum: OsTERGREN 1949; o Festuca arundinacea: BosE MARK 1957; o F estuca pratensis : BosEMARK 1957; o Phleum phleoides: BosEMARK 1957; o Alopecurus pratensis: BosEMARK 1957; o Briza media: BosEMARK 1957; o Holcus lanatus: BosEMARK 1957. The two cases of Phleurn phleoides and P. nodosum (BosEMARK 1957) deserve attention. While the first shows preferential distribution, the second does not present such a phenomenon.…”
Section: Secale Typementioning
confidence: 99%
“…(DHILLON and GARBER 1962) with one to four B's are fertile, but the occurrence of more than four B's produces total sterility.…”
Section: ) Effeci's and Genic Contentmentioning
confidence: 99%
“…4), whose pollen parent had () fragments, demonstrated that at least some pollen carrying many fragments is functional. Dhillon and Garber (1962) have reported that mitotic nondisjunction of supernumerary chromosomes during formation of pollen grains in Collinsia may be responsible for the increase in the number of such chromosomes.…”
mentioning
confidence: 99%